1979
DOI: 10.1002/pssa.2210530216
|View full text |Cite
|
Sign up to set email alerts
|

Velocities of screw and 60° dislocations in n- and p-type silicon

Abstract: The velocities of screw and 60° dislocations in silicon are measured for temperatures ranging from 520 to 800 °C and stresses ranging from 4 to 30 MNm−2 and for various concentrations of phosphorous or boron atoms. n‐doping results in an increase of the velocities of screw and 60° dislocations. In moderately p‐doped Si, no clear effect is observed for screw dislocations while the velocities of 60° dislocations are slightly lower than in intrinsic Si. The effect of doping on the dislocation velocity is discusse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 136 publications
(66 citation statements)
references
References 27 publications
(9 reference statements)
3
63
0
Order By: Relevance
“…metals. Dislocation velocities have been accurately measured in convenient ranges of stress and temperature [3,4], giving a unique opportunity to check the importance of dislocation mobility on the BDT. As a matter of fact, a common view has soon emerged from the works of different groups that dislocation mobility is the rate controlling parameter which determines the critical BDT temperature, T c , at a given loading rate, K. St. John, first, pointed out that an Arrhenius plot of ln K vs. 1/T c yielded an activation energy close to that of dislocation glide.…”
Section: Introductionmentioning
confidence: 99%
“…metals. Dislocation velocities have been accurately measured in convenient ranges of stress and temperature [3,4], giving a unique opportunity to check the importance of dislocation mobility on the BDT. As a matter of fact, a common view has soon emerged from the works of different groups that dislocation mobility is the rate controlling parameter which determines the critical BDT temperature, T c , at a given loading rate, K. St. John, first, pointed out that an Arrhenius plot of ln K vs. 1/T c yielded an activation energy close to that of dislocation glide.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 4 demonstrates that the BDT temperatures obtained in this study at each crosshead speed were overlaid on the temperature dependence of the velocity of a screw dislocation in a silicon single crystal at the resolved shear stress of 20 MPa measured by George and Champier. 19) Here, the BDT temperatures of non-doped silicon obtained in Fig. 1(a) increases as 913 K, 982 K and 1075 K when the crosshead speed was increased by a factor of 10 and 100.…”
Section: Resultsmentioning
confidence: 70%
“…17,18) On the other hand, the effect of p-type dopants, especially the effect of boron, on the dislocation velocity in silicon is not as clear as that of n-type dopants. George and Champier 19) reported that both the dislocation velocity and the magnitude of the activation energy are little influenced by boron at least up to a concentration of 6:8 Â 10 17 atoms/cm 3 . Imai and Sumino measured the dislocation velocity in boron doped silicon and reported the boron doping slightly decreases the dislocation velocity.…”
Section: Introductionmentioning
confidence: 99%
“…Our view is that it is necessary to assess how experimental variables affect the above key variables in order to formulate a DBT model that does not depend on empirical constants. This requires understanding of how confining pressure, 205 radiation enhanced dislocation glide (REDG), 206 impurities, 207 state of stress, 208 and length scale 209 affect dislocation nucleation and mobility. The REDG effect 204 is important since most studies of length scale effects at submicron sizes are accomplished in either SEM or TEM.…”
Section: Future Nanomechanical Approaches To Brittleness Transitionsmentioning
confidence: 99%